On Several Peculiarities Of The Understanding Of Baptism In The Russian Baptist Church - Constantine PROKHOROV (Богословські роздуми: Східноєвропейський журнал богословʼя)
It is no secret that the identical “baptismal texts” of Holy Scripture often receive completely different interpretations in the Western Protestant and Orthodox traditions. More than one-hundred years ago in Russia, at the intersection of West and East, the Russian-Ukrainian Evangelical-Baptist tradition was born, which with time formed itself into a distinctive movement with its own (neither Orthodox nor completely Protestant) theology. The author’s goal is to show the distinctive Slavic Evangelical understanding of water baptism, inevitably basing it not exclusively on New Testament texts but on the Eastern Baptist interpretive paradigm. Many primary sources are consulted: books, articles, hymns, and interviews, in all of which the departure from classical Protestant views on baptism is noted and its meaning in the stream of Eastern tradition—as a sacrament—is followed out.